Motivasi Dan Persepsi Wisatawan Digital Nomad Terhadap Kualitas Pelayanan Di BWork Bali Co-Working Space Kawasan Canggu, Kabupaten Badung - Komang Pretty Again Teja Sari; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2022)
Canggu area is the most popular nomad digital destination among nomad tourists, according to theNomadlist version. The spread of digital nomad tourists has led to the emergence of co-working spaces withvarious facilities called Co-working Spaces. One of the Co-working Spaces that has just started operating in2021, namely BWork Bali Co-working Space, is one of the most sought after by digital nomad tourists inCanggu area, Badung Regency. This study was conducted to determine the characteristics, motivations andperceptions of digital nomad tourists on the quality of service at BWork Bali Co-working Space CangguArea, Badung Regency. This research was conducted by distributing a digital questionnaire in the form of agoogle form to 56 respondents of digital nomad tourists. The results showed that digital nomad tourists atBWork Bali Co-working Space based on their country of origin, namely the United States, worked asentrepreneurs, especially in the digital purview. The motivation of digital nomad tourists at BWork Bali CoworkingSpace got the highest score, namely on the driving variable towards Space and the pull factor onthe Service and Quality variable. Meanwhile, the perception of digital nomad tourists on service quality atBWork Bali Co-working Space obtained Strongly Agree results with an average of 4.67 on Tangible,Empathy, Reliability, Responsive, and Assurance variables.Keyword: service quality, co-working space, digital nomad, motivation, perception